The physiological response of Antarctic fishes to environmental and experimental stress ... - Egginton, Stuart (Société Française d'Ichtyologie, 1997)
From the relatively sparse data available, and on the basis of information from one group of fishes largely endemic to the seas around Antarctica (the red-blooded nototheniids), the stress response would appear to differ from that seen in other teleosts in both quantitative and qualitative aspects. There are unusually small changes in circulating catecholamine levels following induced stress. By contrast, there may be a substantial increase in haematocrit. In the absence of significant adrenergic stimulation this reflects an impressive polycythaemia, due to release of stored red cells from the spleen, rather than red cell swelling. Unlike other teleosts, splenic contraction, and other aspects of cardiovascular physiology, would appear to be largely under cholinergic control. Recovery times are similar to those observed in other fishes, suggesting effective rate compensation for the extreme low temperatures. A reduced glycolytic capacity is reflected in a dominance of respiratory, over metabolic acidosis. ...